Análisis del Rol del Docente de Contaduría Pública en las Universidades de Santa Marta Frente a la Era Digital - Romero Caro, Lorena Estefanie (Universidad Antonio Nariño, 2023)
The general objective of the research was to analyze the role of public accounting teachers in the universities of Santa Marta in the digital era. This qualitative approach study was descriptive and non-experimental. For the realization of this work, the review of bibliographies was used as a data collection technique. Besides, the results shown that technological advances had a positive influence on educators. Where the role of the professor of public accounting changes, to become an advisor and learning guideline, to give the student the opportunity to reply and know how to manage digital resources and educational materials.